(untitled) (Research, Society and Development, 2022)
Soaps are cosmetic detergents, whose basic function is to clean the skin. The formulations and techniques used for soap production are becoming more and more complex due to the enormous number of ingredients and additives that can be used in their manufacture, among them the natural ones. They must be safe and of quality and not harm the environment. Thus, the objective of this work was to develop a natural bar soap containing essential oils and to evaluate its physical-chemical and organoleptic characteristics in order to verify if they meet the requirements for this type of cosmetic. The tests were performed as recommended by Anvisa. The formulation presented a homogeneous aspect, pH within the standard established by Anvisa, good consistency, low alkalinity and free acidity and adequate foaming power. The raw materials used were all natural, which allowed the development of a milder and more sustainable product with the potential to replace products with chemical derivatives. More studies should be carried out in order to verify the stability of the soap developed as a fuction of time.